Clinical Characteristics, Course, and Outcomes of Vertebral Artery Dissections in the Postpartum Period. Issue 5 (November 2021) - Azad, Hooman A; Prasad, Nikil; Shlobin, Nathan A; Mitra, Akash; Cloney, Michael B; Hopkins, Benjamin S; Jahromi, Babak S; Potts, Matthew B; Dahdaleh, Nader S
Abstract : BACKGROUND: : Postpartum vertebral artery dissections (ppVADs) are rare but potentially morbid conditions that occur in otherwise healthy patients. OBJECTIVE: : To evaluate clinical characteristics of ppVADs. METHODS: : Demographic, clinical, treatment, and outcome data were collected on ppVADs and are presented in a case series of 12 patients and compared to the general cohort. RESULTS: : In total, 12 patients had ppVADs in our cohort of 310 patients with vertebral artery dissections (VADs). They occurred 11.27 days (95% CI, −0.85 to 23.39) postdelivery. Of these, there were 5 (42%) with a hypertensive disorder of pregnancy, and 4 (33%) who had migraines. A total of 3 (25%) had ischemic strokes and 1 (8%) had a subarachnoid hemorrhage. In total, 2 patients (17%) had unfavorable modified Rankin Scale (mRS, 2‐6) at discharge from hospital. Patients with ppVADs more often had bilateral VADs (42% vs 17%, P = .03), had pseudoaneurysms (50% vs 18%, P = .0068), were younger (33.83 years vs 44.32 years, P = .018), and had lower Charlson Comorbidity Index (CCI = 0 vs 0.99, P = .0038). Anticoagulant treatment was used in a similar percentage of patients. Multivariate analysis revealed 3 factors were predictive of change in mRS: CCI (OR = 1.09, 95% CI, 1.02‐1.15), stroke (OR = 0.78, 95% CI, 0.65‐0.95), and mRS at hospital discharge (OR = 0.80, 95% CI, 0.74‐0.87). CONCLUSION: : There are only 15 isolated ppVADs reported in the literature; this study adds 12 patients with 17 ppVADs. Postpartum VADs occur in younger, healthier patients than in the general cohort, raising questions about mechanism of injury. The majority of ppVADs have good neurological outcomes. Graphical Abstract : Figure. Graphical Abstract